Pengaruh Media Pembelajaran Berbasis Information and Communication Technology (ICT) Wordwall dan Quizwhizzer Terhadap Minat Belajar Siswa - pratama, Deni Andika Nur; Wahyu Lestari; Darwin Djeni (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2025)
This study aims to examine the effect of the application of ICT learning media based on Wordwall and QuizWhizzer, on students' interest in learning mathematics.The method in this study is quantitative applying a correlation approach with a sample of 38 students of class VIII MTs SA Tarbiyatus Shibyan. Data were collected through observation, questi onnaires, interviews, documentation, and analyzed by applying the Pearson Product Moment multiple correlation test (Correlation Multiple). The results of the study showed that Wordwall has a very strong relationship with students' interest in learning while QuizWhizzer showed a strong relationship . When both media were used simultaneously,  the results of the multiple correlation test showed a very strong relationship with an  result of  and a coefficient of determination , which means the variation in students' interest in learning can be described by the application of Wordwall and QuizWhizzer. Thus, the application of these two media simultaneously has proven effective in optimizing students' interest in learning. Therefore, educators are advised to integrate Wordwall and QuizWhizzer into their learning to develop a more inspiring and responsive learning experience.  Keyword: Information and Communication Technology (ICT) Learning Media Wordwall,  QuizWhizzwer, Learning Interest.